Blueprints: Constructing the Creative Writing PhD - Ella Jeffery, Alex Philp, Emily O’Grady (Queensland University of Technology, 2023)
This article uses architectural analogies to explore the complexities of planning and executing a practice-led PhD project in contemporary Australian writing. Many scholars and creative practitioners have conceived of the writing process as a form of building, scaffolding or construction. A PhD always involves some aspect of planning – but to what extent can the creative practice be planned for? What happens when the project outpaces the planning, or when a writer finds herself in unscaffolded space? This article examines practice-led research methodologies drawn from the experiences and insights of three creative practitioners who are also current and recently-completed PhD candidates. Their perspectives reveal the multiplicity of approaches available in creative practice research and points to the opportunities to explore the complexities between structure, space and practice in discussions of the creative writing PhD.